Perlindungan Hukum Terhadap Anak dari Visual dan Verbal Negatif dalam Game Online di Indonesia - I Gede Arta (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to determine (1) the forms of legal protection that exist in Indonesia in protecting children from negative visual and verbal content in online games, and (2) the legal responsibility of online game electronic system organizers for exposure to negative visual and verbal content in children. The type of research used is normative juridical with a statutory and conceptual approach. The data used are secondary data obtained through document studies, with qualitative descriptive analysis techniques. The results of the study show that legal protection for children from negative visual and verbal impacts in online games is regulated through various regulations, including Law Number 35 of 2014 concerning Child Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions, Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, and Regulation of the Minister of Communication and Information Technology Number 5 of 2021 and Number 2 of 2024. However, its implementation still faces obstacles such as weak age verification, non-objective independent classification, and easily circumvented language filtering. The legal responsibility of online game electronic system organizers for negative visual and verbal content on children can result in administrative or criminal sanctions, according to the Child Protection Law and iRegulation of ithe Minister iof Communication and Information Technology Number 5 of 2021.